VARIASI PADAT TEBAR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN SERUKAN (Osteochilus kappeni) PADA SYSTEM RESIRKULASI - Abdan, Mu'amar; Samsuli, Said; Diansyah, Sufal; Harun, Harun (Universitas Gajah Putih, 2023)
This study aims to analyze the effect of a recirculation system on seurukan fish (Osteochilus kappeni). The research was conducted at UPR Mina Mandiri, Beutong District, Nagan Raya Regency, from January to April 2022. The research design used was a Completely Randomized Design (CRD) with 3 treatment levels and 4 replications, namely: P1 (6 fish/m3), P2 (12 fish/m3), and P3 (18 fish/m3). The analysis of variance (ANOVA) results showed significant effects in all treatments (P>0.05), with the best results obtained in treatment P1. Duncan's multiple range test revealed significant differences among the treatments. The survival rate of the fish in this study ranged from 91.6% to 100%, the weight growth ranged from 1.9 to 4.4 grams, the length of the fish ranged from 5.7 to 7.2 cm, the feed conversion ratio ranged from 19.8 to 32.1, and the coefficient of variation ranged from 18.0 to 27.5. Keywords: recirculation system, seurukan fish, survival rate, growth